دراسة مخبرية على تأثير إعادة الزرع و التعقيم بالحرارة الرطبة على الثبات الأولي للزريعات التقويمية. - خليل, فادي (Latakia University Journal -Medical Sciences Series, 2017)
يزداد دور الزريعات التقويمية كوسيلة دعم في معالجاتنا التقويمية ,هناك حالات عديدة يضطر الطبيب فيها لاعادة استعمال الزريعة التقويمية ( زرعها مرة ثانية ) بعد تعقيمها بالحرارة الرطبة, كان الهدف من البحث : تقصي أثر إعادة الزرع مرة ثانية و التعقيم بالحرارة الرطبة على الثبات الأولي للزريعة ,تم استعمال طولين للزريعات(6-7 ملم) (ti – 6A1 – 4A1 ) وشكلين ( عادي و ثنائي الحلزنة) وادخالها في العظم الصناعي ( saw bone ) مرة أولى ثم مرة ثانية بعد تعقيمها بالحرارة الرطبة ( Autoclave) بزاوية ادخال 90 درجة وتم قياس تورك الإدخال وتورك الإخراج وقياس البريوتيست ( اختبار النسج حول السنية ) لتقييم الثبات الأولي( بعد الزرع أول مرة و ثاني مرة بعد التعقيم) تبين النتائج : نقص في الثبات الأولي بعد إعادة الزرع و التعقيم بالحرارة الرطبة ولكن يبقى ضمن حد يسمح باستعمالها مرة ثانية بفعالية لتأمين الدعم التقويمي اللازم وذلك لكلا الطولين والقطرين There is an increasing role for orthodontic mini implants as an anchorage device in orthodontic practiceIn many occasions, orthodontists may have to reuse orthodontic mini-implants (re-implanting again ) after sterilizing them by moist heat.The aim of this research was investigating the effect of re-implantation and moist heat sterilization on the primary fixity of orthodontic mini-implants>Two lengths of mini-implants (6-7mm) (ti – 6A1 – 4A1 ) and two shapes (normal and dual thread ) were used and inserted in artificial bone (saw bone ) a first time and after sterilizing them by moist heat (Autoclave) a second time , in an insertion angle of 90 .The insertion and removal torque and periotest score (periodontium test device ) were measured to assess the primary fixity ( after implanting in the first time and the second time )The results showed a decrease in the primary fixity after re-implanting and sterilizing by moist heat , but it still enough for using it a second time effectively to provide needed orthodontic anchorage for both two lengths and two shapes.